Draft Genome Sequence of Pseudomonas aeruginosa Strain ATCC 27853 - Fang, Xiangqun (American Society for Microbiology, 2012)
Pseudomonas aeruginosa is a common bacterium that can cause disease. The versatility of Pseudomonas aeruginosa enables the organism to infect damaged tissues or those with reduced immunity which cause inflammation and sepsis. Here we report the genome sequence of the strain ATCC 27853.